One-dimensional compression behavior of calcareous sand cemented with EICP and coir fiber - Xueliang Jiang; Haodong Wang; Hui Yang; Jun Yin; Bo Shen (Scientific Reports)
Abstract Calcarenite sand, as a key geotechnical material in the construction of South China Sea islands and reefs, is limited in its engineering applications due to its significant high compressibility characteristics. This study proposes a treatment method combining Enzyme-Induced Calcium Carbonate Precipitation (EICP) with coir fiber. Through a series of one-dimensional compression tests, the effects of different grouting times (0, 3, 6, 9), coir fiber contents (0%, 0.2%, 0.4%, 0.6%, 0.8%), and relative densities (30%, 60%, 90%) on the compressive characteristics of calcarenite sand were systematically investigated. The research findings indicate that as the number of EICP grouting cycles increases, the reduction in the void ratio of the samples gradually diminishes. Under the same conditions, the addition of coir fiber initially leads to a decrease in the reduction of the void ratio, followed by an increasing trend. The experimental data under various conditions were successfully fitted using the Harris function, elucidating the relationships between the model parameters b and c and the factors of calcium carbonate content, coir fiber content, and initial void ratio. Additionally, the Lasso regularization method was employed, and a polynomial model equation was established using Matlab software based on the method of defining training and testing datasets (with the parameter b as a 4th-order polynomial and the c as a 3rd-order polynomial). Validation demonstrated that the constructed model equations possess high predictive accuracy and generalization capability. This study not only deepens the understanding of the one-dimensional compressive deformation of calcarenite sand under the synergistic effect of coir fiber and EICP technology, but also provides a theoretical basis for the rapid assessment and optimization of the compressive characteristics of calcarenite sand foundations in the construction of South China Sea islands and reefs.